SINERGITAS ORANG TUA DAN GURU DALAM MENUMBUHKAN PRESTASI PESERTA DIDIK DI SD ISTIQAMAH - Naili Nur Aini Yulikah; Khalimatul A’isah; Amalia Khamidah; Zaida Taqiyya Adiba; Umi Hanik Umi Hanik (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Education is very important for everyone, combined with the synergy between parents and teachers, the learning process will be better. because students feel cared for in their learning. At Istiqamah Elementary School itself, education is what people born into the world should receive and who prioritize the best for their students. Thus, the participation of parents and teachers in education can contribute to the growth of student achievement at SD Istiqamah. This study aims to determine the synergy of parents and teachers in growing student achievement in SD Istiqamah. The research method used is descriptive qualitative approach and data collection method with the proposed location observation, namely SD Istiqamah and image documentation. The results showed that parents act as mentors, modelers and teachers. While the teacher acts as a motivation, demonstrator and evaluation. Synergy implementation is carried out by parents and teachers to improve student performance through reciprocal communication between teachers and parents, participation in parent and teacher involvement in student education, participation in decision making. Thus the synergy of parents and teachers in growing student achievement at SD Istiqamah is very necessary, because student success does not only come from themselves, but also from teachers, and parents who always support their education